2001
DOI: 10.1080/00498250110079149
|View full text |Cite
|
Sign up to set email alerts
|

Plasma concentrations of individual tea catechins after a single oral dose in humans

Abstract: 1. Ten healthy volunteers ingested 1.5 mmole epicatechin gallate (ECg), epigallocatechin (EGC) or epigallocatechin gallate (EGCg) in a randomized crossover design. After deconjugation, catechins in plasma and 24-h urine samples were determined by high-performance liquid chromatography (HPLC). Antioxidant activity was measured in plasma by determining ferric reducing activity (FRAP). 2. The catechin levels in plasma after ingestion were significantly different: EGC rose quickly with a short elimination half-lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(97 citation statements)
references
References 12 publications
8
86
1
2
Order By: Relevance
“…Doxorubicin-resistant cells MDA-MB-231 (231DXR) and HCC1806 (HCCDXR) were developed using a stepwise selection method. Increasing doses of doxorubicin (TEDEC-Meiji Farma) were performed until their corresponding IC 50 was reached. Briefly, initially cells were treated with a concentration of doxorubicin of 0, 1Â IC 50 .…”
Section: Methodsmentioning
confidence: 99%
“…Doxorubicin-resistant cells MDA-MB-231 (231DXR) and HCC1806 (HCCDXR) were developed using a stepwise selection method. Increasing doses of doxorubicin (TEDEC-Meiji Farma) were performed until their corresponding IC 50 was reached. Briefly, initially cells were treated with a concentration of doxorubicin of 0, 1Â IC 50 .…”
Section: Methodsmentioning
confidence: 99%
“…EGCG is found at very low levels, if at all, in urine [207,211,212] and interconversion or de-gallation from EGCG to EGC is very limited [211].…”
Section: Effects On Ttr Toxicity In Vivomentioning
confidence: 99%
“…Studies on bioavailability are often conducted collecting specimens at timed intervals (after ingestion). Various studies have been conducted using normally prepared green tea beverages [14][15][16], ingested green tea extract (total catechins) [14,17,18], or ingestion of specific catechins [19][20][21]. These studies have shown that ECG and EGCG, and metabolites of EC and EGC can be detected and measured in blood plasma.…”
Section: Introductionmentioning
confidence: 99%